Innovative Visualization Tools to Monitor Scientific Cooperative Activities - Otjacques, Benot; Noirhomme, Monique; Feltz, Fernand (CDVE'07: Proceedings of the International Conference on Cooperative Design, Visualization, and Engineering, 2007)
This paper describes how information visualization techniques can be used to monitor a web-based collaborative platform and to support workplace awareness by providing a global overview of the activities. An innovative prototype is described. Its originality relies on using some enclosure-based visualization methods in the context of activities monitoring, which is rather unusual. In addition, a new layout is described for representing data trees. The use of the system is illustrated with the case of a EU-funded Network of Excellence.